Authentic leadership, neurodiversity inclusion climate and information asymmetry: Two- and three-way interaction effect on constructive voice behaviours - Hannah Esi Akyere Acquah; Rejoice Esi Asante; Esther Julia Korkor Attiogbe (Social Sciences and Humanities Open)
Authentic leadership is recognised for its ability to foster constructive voice behaviours, yet the conditions shaping this relationship remain underexplored. Drawing on conservation of resources theory and social cognitive theory, we examine how neurodiversity inclusion climate and information asymmetry moderate the effectiveness of authentic leadership in encouraging proactive employee behaviours. Through the lens of resource pathways, we argue that authentic leadership creates a psychologically safe environment that motivates employees to engage in constructive voice behaviours. We further propose that neurodiversity inclusion climate acts as a resource-enabling factor, enhancing the positive effects of authentic leadership, while information asymmetry serves as a resource-depleting condition, constraining this relationship. Using a time-lagged survey design and data from 593 healthcare professionals in Ghana, analysed through partial least squares structural equation modelling (PLS-SEM), our findings provide robust support for these propositions. Authentic leadership positively influences constructive voice behaviours, with neurodiversity inclusion climate amplifying this effect and information asymmetry diminishing it. Moreover, a three-way interaction reveals that the strongest leadership-voice link occurs when neurodiversity inclusion climate is high and information asymmetry is low. Our study contributes to leadership theory by uncovering the complex interplay of leadership behaviours, inclusivity, and informational clarity, offering actionable insights for fostering employee voice behaviours in resource-constrained healthcare settings.